Cannabinoids for behavioral symptoms in severe dementia: Safety and feasibility in a long-term pilot observational study in nineteen patients - Pautex, Sophie; Bianchi, Federica; Daali, Youssef; Augsburger, Marc; de Saussure, Christian; Wampfler, James; Curtin, François; Desmeules, Jules; Broers, Barbara (Frontiers in Aging Neuroscience, 2022)
Context: The management of the behavioral symptoms and rigidity in patients with dementia constitutes a significant challenge. Short-term studies suggest an interest in the use of medical cannabis, but long-term data are lacking. Objectives: To investigate the feasibility and long-term safety of administering THC/CBD treatment as an additional drug to a poly-medicated population with severe dementia, evaluate clinical improvements, and collect information on the pharmacokinetics of cannabinoids and possible drug-drug interactions. Methods: A prospective observational study of patients with severe dementia living in a long-term care home to whom the physicians had prescribed a medical cannabis treatment. Data were collected over two years. Assessments of the changes in medical cannabis dosages, safety parameters, and variations in neuropsychiatric problems, agitation, rigidity, the most invalidating daily activity, and disabling behavior trouble scores. Evaluation of the pharmacokinetics of cannabinoids by measuring plasma levels and analyzing enzymatic activity. Results: We assessed 19 patients (81.4 years- 17 females, 2 men) receiving an average of 12.4mg THC/24.8mg CBD per day for up to 13 months, with no reported problems related to the treatment and limited adverse drug reactions. Clinical scores showed a marked improvement that was stable over time, de-prescription of other medications and care facilitated. The pharmacokinetic evaluation showed an expected slight reduction in the enzymatic activity of CYP1A2 and CYP2C19. Conclusion: A long-term THC/CBD (1:2) medication can be administered safely and with overall positive clinical improvement to poly-medicated older adults with severe dementia and associated problems. Results must be confirmed in a randomized trial.